Town planning and public housing - Miguel Angel Arteaga Castro (European Regional Science Association (ERSA), 1998)
During the last seven years, Spain has experience importans legislativies changes in land and housing materia. The land law of 1990, conceive the urbanistic proficience as colectivity result and the cession of part of this proficience to the land owner. This law changes the point of view about the land ownership. The use of this legislation with the objetive to maximice the colectivity utility to a minimun ejecutation cost and the transfer of the proficience from some town zones to others, building systems of distribution of charges and benefits. The city of Cadiz is a particular case where is used and checked. With the housing legislation has been posible the creation of public housing companies, perfect complement to the public intervencion in thats materials. A special case is the San Fernando public housing company (Cadiz) with the objetive of intervention in the low rent housing market without cost for the Local Administration. Keywords: Town Planning, Public Intervention, Housing.
Keywords: 330